Pengaruh Literasi Keuangan terhadap Kinerja Karyawan serta Dampaknya terhadap Kinerja Keuangan pada Bank Syariah Indonesia KCP Blangpidie - Rika Agustina Misda; Chairiyaton Chairiyaton (Pusat Riset dan Inovasi Nasional, 2024)
Financial performance is an important indicator used to evaluate the financial condition of an entity, such as a bank. Financial performance evaluation provides an understanding of an entity's financial health, operational efficiency, profitability, and financial sustainability. This research aims to comprehensively investigate the influence of financial literacy on employee performance and its impact on financial performance in the Islamic banking environment. This research uses quantitative methods with descriptive analysis methods. The population and sample in this study were all employees at BSI KCP Blangpidie, namely 35 people. The data used in this research is primary data obtained from the results of distributing questionnaires. The analysis used in this research is path analysis. The research results show that financial literacy has a positive and significant influence in improving financial performance at BSI KCP Blangpidie, this is because the calculated t value is greater than the t table (9.074 > 2.034). Likewise, from the calculations that have been carried out, it is known that the direct effect is 0.346 and the indirect effect is 0.591, which means the direct effect is smaller than the indirect effect.